Analysis of the Utilization of the Office Administration Automation Laboratory (Studies on Archival Subjects Class X) during the Covid-19 Pandemic at UPT SMK Negeri 1 Bulukumba - Arhas, Sitti Hardiyanti; Syazwani, Syazwani; Nasrullah, Muh. (Pinisi Journal of Education and Management, 2022)
Abstract. The process of teaching and learning activities in the Office Governance Automation Expertise Competence can be in the form of theory or practice, students can carry out teaching and learning activities in the classroom and practicum (laboratory). This research is descriptive research using a qualitative approach. With five subjects, namely, the head of the OTKP laboratory, archiving subject teacher, and 3 students at SMK Negeri 1 Bulukumba. Data collection techniques using observation methods, interview methods, and documentation methods. Data analysis techniques in this study used data reduction techniques, data presentation, conclusions, and verification. The results showed that the Analysis of the Utilization of the Office Administration Automation Laboratory (Class X Archival Subject Study) during the Covid-19 Pandemic at UPT SMK Negeri 1 Bulukumba, had been put to good use. This can be seen from the four indicators, namely independent and guided learning, using teaching materials in digital form, utilizing information and communication technology-based learning media, and implementing information and communication technology-based learning interactions by minimizing direct interactions.